Predicting Crown-width of Dominant Trees on Teak Plantation from Clonal Seed Orchards in Ngawi Forest Management Unit, East Java - Ronggo Sadono (Jurnal Ilmu Kehutanan)
AbstractThis study aims to determine the model of crown width development of the dominant teak tree planted using seeds from clonal seed orchards. The research was carried out in Ngawi Forest Management Unit on the good quality teak compartment having stands age from 6 to 15 years old. The good quality compartments were determined based on higher stand density, taller average tree height, larger average stem diameter, and good accessibility. In a well-qualified compartment, 30 samples of the dominant tree were selected and each sample was measured for the crown radius in the four radii. The measured crown radius was used to calculate average crown radius as a quadratic mean of 4-crown radii and crown width as double of average crown radius. The arithmetic mean of the crown width of the 30 dominant trees in each measured compartment was used as the response variable and stand age as the predictor variable. The measurement data were then sorted into two parts, namely: mostly for model fitting and the remaining for model validation. Non-linear regression analysis with the least squares method was used to evaluate 4 candidate models of average crown width, namely: Sigmoid, Power, Schumacher, and Gompertz models. The model selection was based on the highest coefficient of determination and the smallest standard error of the estimate and the significance of F test and T test. The best model was eventually validated using the following criteria : root mean squared error, aggregate deviation, and relative deviation. Gompertz model was the best model to predict the average crown width development of dominant teak tree and expressed as: CW = 6.585 Xe-0.705xe-0.091xage and able to explain 79% variation of data. The model was passed based on statistical validation and it was feasible for predicting the average of crown width of dominant teak tree from clonal seed orchards on good quality stand aged 6 to 15 years in Ngawi Forest Management Unit.